Differentiation of Low-Grade Astrocytoma From Anaplastic Astrocytoma Using Radiomics-Based Machine Learning Techniques - Chen, Boran; Chen, Chaoyue; Wang, Jian; Teng, Yuen; Ma, Xuelei; Xu, Jianguo (Frontiers in Oncology, 2021)
Purpose: To investigate the diagnostic ability of radiomics-based machine learning in differentiating atypical low-grade astrocytoma (LGA) from anaplastic astrocytoma (AA). Methods: The current study involved 175 patients diagnosed with LGA (n=95) or AA (n=80) and treated in the Neurosurgery Department of West China Hospital from April 2010 to December 2019. Radiomics features were extracted from pre-treatment contrast-enhanced T1 weighted imaging (T1C). Nine diagnostic models were established with three selection methods (Distance Correlation, least absolute shrinkage, and selection operator (LASSO), and Gradient Boosting Decision Tree (GBDT)) and three classification algorithms (Linear Discriminant Analysis (LDA), Support Vector Machine (SVM), and random forest (RF)). The sensitivity, specificity, accuracy, and areas under receiver operating characteristic curve (AUC) of each model were calculated. Diagnostic ability of each model was evaluated based on these indexes. Results: Nine radiomics-based machine learning models with promising diagnostic performances were established . For LDA-based models, the optimal one was the combination of LASSO + LDA with AUC of 0.825. For SVM-based modes, Distance Correlation + SVM represented the most promising diagnostic performance with AUC of 0.808. And for RF-based models, Distance Correlation + RF was observed to be the optimal model with AUC of 0.821. Conclusion: Radiomic-based machine-learning has the potential to be utilized in differentiating atypical LGA from AA with reliable diagnostic performance.